Pematangan Gonad Calon Induk Ikan Selincah (Belontia hasselti Cuvier, 1831) dengan Tingkat Kepadatan Berbeda di Embung Sriwijaya - Danang Yonarta; Tanbiyaskur Tanbiyaskur; Mochamad Syaifudin; Dwi Inda Sari; Rupi Sanjaya (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
The domestication of java combtail (Belontia hasselti Cuvier, 1831) has not been carried out so far, its existence in nature is getting less and less. This causes the domestication of java combtail to be very important, so that it can maintain sustainability and meet market demand for these fish. Stocking density is one of the factors that influence the development of gonadal maturity levels. The purpose of this study was to determine the best stocking density in the maturation of java combtail broodstock. This research was conducted at the Sriwijaya Reservoir, Aquaculture Laboratory and Experimental Ponds, Department of Fisheries, Universitas Sriwijaya. The test fish used were obtained from the catch of fishermen in the swamp area on the Belida River, Gumai Village. The results of the rearing of java combtail with different stocking densities in P2 treatment significantly affected the male gonad maturity index of 1.11±1.63% and females of 13.91±17.06%, male gonad index of 7.98±10 .53 and females 81.63±107.54, fecundity of 4174±4884 eggs and egg diameter of 40.34±45.97 m. Meanwhile, the maturity level of fish gonads was faster, especially in female java combtail (B. hasselti Cuvier, 1831) at TKG IV.